Horn radiators of complex configuration - I.I. Shumljansky (World Scientific, 1993)
An important class of antenna devices - horn radiators - is discussed in this book. The author aims to synthesize and classify the plentiful materials that are scattered over short-run publications, and present to the readers an up-to-date conception of this problem